The first recorded outbreak of cryptosporidiosis due to Cryptosporidium cuniculus (formerly rabbit genotype), following a water quality incident - Puleston, Richard L.; Mallaghan, Cathy M.; Modha, Deborah E.; Hunter, Paul R.; Nguyen-Van-Tam, Jonathan S.; Regan, Christopher M.; Nichols, Gordon L.; Chalmers, Rachel M. (IWA Publishing, 2014)
Background: We report the first identified outbreak of cryptosporidiosis with Cryptosporidium cuniculus following a water quality incident in Northamptonshire, UK. Methods: A standardised, enhanced Cryptosporidium exposure questionnaire was administered to all cases of cryptosporidiosis after the incident. Stool samples, water testing, microscopy slides and rabbit gut contents positive for Cryptosporidium were typed at the Cryptosporidium Reference Unit, Singleton Hospital, Swansea. Results: Twenty-three people were microbiologically linked to the incident although other evidence suggests an excess of 422 cases of cryptosporidiosis above baseline. Most were adult females; unusually for cryptosporidiosis there were no affected children identified under the age of 5 years. Water consumption was possibly higher than in national drinking water consumption patterns. Diarrhoea duration was negatively correlated to distance from the water treatment works where the contamination occurred. Oocyst counts were highest in water storage facilities. Conclusions: This outbreak is the first caused by C. cuniculus infection to have been noted and it has conclusively demonstrated that this species can be a human pathogen. Although symptomatically similar to cryptosporidiosis from C. parvum or C. hominis, this outbreak has revealed some differences, in particular no children under 5 were identified and females were over-represented. These dissimilarities are unexplained although we postulate possible explanations.